PRACTICING VALUES OF PHILOSOPHICAL SUFISM IN THE PENCAK SILAT OF BROTHERHOOD FAITHFUL HEART OF TERATE - Sutoyo (European journal for philosophy of religion, 2023)
Purpose: Pencak silat has been a part of Indonesia's cultural heritage imparting lessons in Islamic morality, in addition to self-defense, cultural arts, sports, and mental and spiritual training. Members are trained in these skills along with Islamic religious lessons and the Sufi philosophy. Previous studies have however shown a grey side of pencak silat, which involved violence with other groups, and not the Sufi and the spiritual teachings. The current study, therefore, aimed to examine the Sufism in PSHT’s pencak silat and how its members practiced the teaching of Sufism and Islamic philosophy. Qualitative ethnographic research approach was used, with observation, semi-structured interviews, and documentation as data collection instruments. Finds show that Sufism in PSHT means mastering a control over heart or mind, showing good behavior, de-radicalizing religion, and learn the meaning of life to develop spiritual intelligence. It was also evident in the study that Sufism can strengthen Muslim members' faith and aqidah as it also teaches religious tolerance towards non-Muslims. It strengthens inner relationships, builds noble character, preserves nature and peace, and increases ma'rifah knowledge by drawing closer to God. This research recommends that the government should support mental spiritual, cultural arts, martial arts, and sports in all pencak silat organizations in Indonesia and preserve the cultural heritage to benefit the nation, state, and society